(untitled) (Journal of Psychiatrists’ Association of Nepal, 2021)
INTRODUCTION Electroencephalography is a safe, convenient, non-invasive, and inexpensive technique that allows assessment of cerebral function and detects physiological manifestations of abnormal cortical excitability. Published literature about its utilization and application is sparse from this part of the world. METHODOLOGY It is a descriptive, cross-sectional study conducted in Nepalgunj Medical College, Kohalpur, Nepal. All the subjects referred for EEG evaluation from January 2019 to December 2020 (two years) were enrolled and EEG was performed. A self-designed proforma was used to record different variables and data was analyzed using Statistical Package for the Social Sciences version 21.0 for Windows. RESULT Of total 246 subjects, 53.3% were male and 58.9% of the subjects were 20 years or younger by age. Maximum (35.8%) number of referrals came from the department of psychiatry. Generalized seizure discharge was the most common EEG diagnosis and presence of seizure activity was noted in 37%of patients. CONCLUSION EEG is utilized by different specialities commonly for seizure disorder, psychiatric disorders and headaches.